Clinical profile of primary hyperparathyroidism in Northeast India: a single centre experience - Sarma, Dipti; Saikia, Uma K.; Appaiah, Sonali (International Journal of Research in Medical Sciences, 2019)
Background: A retrospective study of the presentation of primary hyperparathyroidism was done at a tertiary care centre in northeast India and was compared with variable features in other parts in India and worldwide. Methods: The clinical presentation, biochemical parameters, radiological and histopathology findings of 27 subjects of primary hyperparathyroidism who presented to us over a period of 5 years were retrospectively analysed. Chi-square test, student t test and ’one way ANOVA’ were used to compare different variables. Statistical significance was set at p<0.05. Results: The age distribution ranged from as young as 13 years to 72 years (39±16.7). The male:female ratio was 1:1.25. The duration of symptoms at presentation ranged from 2 to 72 months (21.7±20.3). The most common presentation was bone pain in 59.2% of cases, followed by proximal myopathy (48.1%), fatigue (44.4%), abdominal pain (44.4%), constipation (11.1%), hypertension (18.5%), palpable neck swelling (22.2%), limb deformity (22.2%) and fracture (14.8%). The mean serum calcium was 12.2±0.87mg/dl. Parathyroid adenoma was localized radiologically in all patients and single adenoma was the most common cause in 96.3%. Left inferior parathyroid adenoma was the most common site of involvement in 51.8%. Conclusions: Hyperparathyroidism at our centre in northeast India has a classic symptomatic presentation with severe bone and renal involvement and younger age at diagnosis, and equal gender distribution.